Views of Uzbeks About the Human Soul - Muqaddas Khabibullaevna, Payzieva (Researchparks Publishing, 2023)
The article reveals on the basis of ethnographic and scientific literature that Uzbeks' views and ideas about death, human spirit and soul are connected with their ancient religious ideas. The article also highlights the views of fraternal peoples.